Mapping international scientific production on social diversity in the context of ESG: A bibliometric study comparing research from high income and middle/low-income countries - Da Silva, Mariana; Prevot, Frédéric; Nascimento, Luis (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2025)
The social dimension of Environmental, Social and Governance (ESG) practices fosters diversity and inclusion, contributing to more sustainable work environments. However, approaches vary across countries in terms of compliance and the attention given to this dimension. This article examines whether academic research reflects such differences. Using a bibliometric analysis, we map international scientific production on social diversity in the ESG context, relying on VOSviewer and Biblioshiny. We provide a historical and comparative overview of countries, authors, and journals, highlighting central research themes. The study underscores differences and similarities in keywords, with a particular focus on the contrasts between high-income and middle- or low-income countries.